Global research trends in necrotizing pancreatitis: a bibliometric analysis from 2013 to 2024 - Gainollina, Gulnur G.; Jakanov, Murat K.; Zhakiev, Bazylbek S.; Karsakbayev, Uteugaly G.; Taishibayev, Kairat R.; Kurmanbayev, Bulat A. (Frontiers in Medicine, 2025)
BackgroundThis study aims to analyzing scientific publications related to necrotizing pancreatitis and its mortality, identifying key areas and trends, and determining the leading research institutions, authors, countries, and journals actively working in this field.MethodsThe Web of Science and Scopus databases were searched for articles on NP published between January 1, 2013, and April 22, 2024. Articles published before 2013, conference abstracts, and case reports were excluded. The articles were assessed based on various metrics, including the number of citations, publication dates, countries of origin, institutions, journals, and authors.ResultsA total of 929 articles were identified, of which 251 were deemed suitable for analysis after duplicates were removed. China contributed the most articles, followed by the United States and India. The most frequent publications appeared in specialized journals such as “Pancreatology” and “Journal of Gastrointestinal Surgery.” The primary research institutions were universities and medical centers. The highest-impact articles focused on minimally invasive treatment methods for NP. There has been a growing body of research in NP over the past decade, particularly in China and the United States.ConclusionDespite advancements in medical science, the mortality rate associated with pancreatic necrosis remains high. This highlights the continued challenge in effectively addressing complications of acute pancreatitis. Researchers worldwide are actively exploring alternative therapeutic approaches to mitigate these complications and improve patient outcomes.